Pupil dilation betrays the timing of decisions - Einhauser, Wolfgang; Koch, Christof; Carter, Olivia (Frontiers in Human Neuroscience, 2010)
The notion of "mind-reading" by carefully observing another individual's physiological responses has recently become commonplace in popular culture, particularly in the context of brain imaging. The question remains, however, whether outwardly accessible physiological signals indeed betray a decision before a person voluntarily reports it. In one experiment we asked observers to push a button at any time during a 10-second period (“immediate overt response”). In a series of three additional experiments observers were asked to select one number from five sequentially presented digits but concealed their decision until the trial’s end (“covert choice”). In these experiments observers either had to choose the digit themselves under conditions of reward and no reward, or were instructed which digit to select via an external cue provided at the time of the digit presentation. In all cases pupil dilation alone predicted the choice (timing of button response or chosen digit, respectively). Consideration of the average pupil-dilation responses, across all experiments, showed that this prediction of timing was distinct from a general arousal or reward-anticipation response. Furthermore, the pupil dilation appeared to reflect the post-decisional consolidation of the selected outcome rather than the pre-decisional cognitive appraisal component of the decision. Given the tight link between pupil dilation and norepinephrine levels during constant illumination, our results have implications beyond the tantalizing mind-reading speculations. These findings suggest that similar noradrenergic mechanisms may underlie the consolidation of both overt and covert decisions.